Effects of grazing on plant functional groups across spatial scales in Stipa breviflora desert steppe - Wang, Li; Du, Xiaoyu; Liu, Juhong; Zhang, Jun; Lv, Shijie (Frontiers in Plant Science, 2025)
This study investigated the Stipa breviflora desert steppe through multi-scale (50m×50m, 25m×25m, 2.5m×2.5m) and grazing intensity (no grazing vs. heavy grazing) comparative analyses, revealing the response mechanisms of plant functional group diversity, interspecific associations, and stability. Key findings include: (1) Heavy grazing significantly reduced functional group diversity and evenness, while the Margalef richness index increased at the 25m×25m scale due to patchy invasion of grazing-tolerant species. (2) Interspecific associations exhibited scale-dependent patterns: Large-scale (50m×50m) associations were driven by environmental heterogeneity (e.g., resource competition and complementarity), whereas small-scale (2.5m×2.5m) interactions were dominated by direct species interactions (mutualism or exclusion). (3) Grazing-induced structural simplification through “environmental filtering”, heavy grazing reduced functional group quantity, forming simplified symbiotic networks (PC≥0.6) between perennial grasses and annual/biennial plants, while significantly suppressing woody plants and forbs (Perennial forbs, Shrubs and semi-shrubs). (4) Stability analysis demonstrated higher stability of perennial grasses and forbs in ungrazed areas, though the overall system remained unstable. Annual/biennial plants and shrubs/semi-shrubs generally exhibited low disturbance resistance. The study proposes a multi-scale grassland restoration strategy: optimizing resource allocation at large scales while enhancing key species interactions at small scales. These findings provide theoretical foundations for the ecological restoration of degraded desert steppes and adaptive grazing regimes. Future research should integrate climate change and socioeconomic factors to develop more resilient grassland ecosystem management frameworks.